Electrical, Thermal and Mechanical Properties of Epoxy/CNT/Calcium Carbonate Nanocomposites - Backes,Eduardo Henrique (2018)
Epoxy/CNT and epoxy/CNT/calcium carbonate nanocomposites were produced via in situ polymerization assisted by ultrasonication without solvent and electrical, mechanical, thermal and thermomechanical properties of nanocomposites were evaluated. Epoxy/CNT presented very low percolation threshold, near 0.05 wt % and nanocomposites with higher contents of CNT presented further increase in electrical conductivity. The addition of calcium carbonate in epoxy/CNT nanocomposites increased the electrical conductivity, due to volume exclusion phenomena. Regarding thermal properties, due to the low content of the CNT and calcium carbonate no changes in glass transition (Tg) were observed. DMA results showed no significant changes in thermomechanical properties, once the contents of CNT and calcium carbonate are below stiffness threshold, however an increase of flexural modulus by adding CNT and calcium carbonate was observed.